Benthic seaweed from Isla Cozumel, Quintana Roo, Mexico - Mateo-Cid, Luz Elena; Mendoza-Gonzalez, Angela Catalina (Instituto de Ecología, A.C., 1995)
Results are presented of a study on benthic marine algae from the Caribbean waters, of Cosumel island, Quintana Roo, Mexico. The floristic list includes data on distribution of species, reproductive stage, tidal level, mode, facies, and epiphytism. 22 species of Cyanophyceae, 167 species and 1 form of Rhodophyceae, 35 species and 1 variety of Phaeophyceae, 19 species of Bacillariophyceae and 79 species, 1 variety and 9 forms of Chlorophyceae were identified. Species diversity was compared for two different climatic seasons, the rainy and the dry, during 1970, 1983, 1984 and 1985. Differences in the total number of species found in each climatic seasons were significant. The algal flora of Cozumel island is tropical and the greatest diversity was found in the rainy season. Species diversity in relation to temperature, light, facies and tides is discussed.